Malar reshaping technique using bidirectional barb thread suspension procedure for 3-dimensional aging in Asian faces - Kwun Cheung Hau, MBChB, MRCP, FHKCP, FHKAM, DCH; Suyog Jain, MD (Wolters Kluwer, 2021)
Background: Aging is a natural process that causes skin texture changes, facial volume loss, and altered 3-dimensional topography of the underlying tissues.Objective: The aim of this study is to assess the malar reshaping strategy in Asian patients using bidirectional suspension-barbed threads.Methods: A prospective interventional study was conducted on Asian patients presenting with mild-to-moderate facial aging who were treated with the Definisse double-needle thread in the Hong Kong Special Administrative Region. The primary endpoint was assessed using the Global Aesthetic Improvement Scale and scoring the benefit of anterior projection using a questionnaire. Patient safety was the secondary endpoint measured.Results: Twenty Asian patients (4 men [20%] and 16 women [80%]; age <45 to ≥45 years) were included in the study. The patients experienced marked improvement (score 2) in their appearance, except for the follow-up after 1 month. One month after the procedure, patients scored 1 for optimal cosmetic improvement in their looks. The nasolabial fold disappeared in all patients (n = 20 [100%]) and the face looked slimmer. Nine patients (45%) reported that the focus seemed centralized. Four patients (20%) reported prominence of the nose and chin. Redness, swelling, and bruising were the most common adverse events experienced by 75% of patients (n = 15), followed by pain (n = 6; 30%). All adverse events resolved within 4 weeks after their incidence. Because 80% of our patients were women, these positive cosmetic outcomes may be of interest across the aging female population.Conclusion: Overall, 3-dimensional facial rejuvenation with the Definisse thread seems to be an effective, safe, and minimally invasive office-based procedure to achieve immediate and long-term effects. These absorbable barbed sutures used in the malar reshaping technique can result in satisfactory esthetic enhancement of 3-dimensional aging, including sagginess, jowling, central facial heaviness, and tissue descent in female and male Asian patients.